Contrast-induced nephropathy - prevention and treatment - Mateusz Bajak; Julia Słowik; Daniel Zapasek; Michał Szczepański; Maciej Mamczur; Dominik Maciej Feret; Jadwiga Inglot; Julia Inglot; Marcin Kuliga; Damian Sowa; Katarzyna Widawska (Quality in Sport, 2024)
Introduction and purpose: Contrast-induced nephropathy (CIN) is kidney damage that can occur after the administration of contrast agents used in medical imaging procedures like angiography and CT scans. The exact mechanism is not fully understood but is believed to involve direct toxic effects, changes in kidney blood flow, and inflammation. Diagnosis is based on increased serum creatinine levels after contrast exposure. CIN poses challenges due to the rising use of contrast imaging, an aging population, and the increasing prevalence of chronic conditions like diabetes and hypertension. The Aim of this article is to summarize information on how to  prevent contrast-induced nephropathy. Review of medications and pre-procedural screening and monitoring helpful to lower risk of CIN.